Coagulopathy as a Complication of Cardiopulmonary Arrest Following Balloon Valvuloplasty in a Dog - Marissa A. Turner; Theresa C. Hallowell (Veterinary Medicine and Science, 2025)
ABSTRACT Objective To describe successful management of a coagulopathy secondary to cardiopulmonary arrest (CPA) associated with pulmonary balloon valvuloplasty. Case Summary An 8‐month‐old male intact Chihuahua mix presented for a pulmonary balloon valvuloplasty. Echocardiogram showed severe valvular pulmonic stenosis with a pulmonic valve maximum pressure gradient (PV max ΔP) of 108.2 mmHg (PV max ΔP >20 mmHg is considered abnormal). Near the end of the procedure, after the balloon deflation, the patient experienced prolonged periods of sinus arrest with associated ventricular escape rhythm. This was followed by complete sinus arrest and asystole. Cardiopulmonary resuscitation (CPR) was initiated. After four CPR cycles, return of spontaneous circulation was achieved. The patient continued to have hypotension despite fluid resuscitation, requiring vasopressor therapy. Hemorrhagic abdominal effusion was identified. Coagulopathy was confirmed via prolonged blood clotting times and thrombocytopenia. Treatment was comprehensive, including transfusions of whole blood, packed red blood cells and fresh frozen plasma. During 4 days of postoperative hospitalisation, the patient showed improvement and was discharged. Upon rechecking 13 and 227 days after discharge, a repeated echocardiogram showed a >50% improvement of the PV max ΔP measured at 40 and 38.5 mmHg, respectively. New or Unique Information Provided This is the first published veterinary case report describing the recognition and successful treatment of a consumptive coagulopathy and presumptive disseminated intravascular coagulation (DIC) following CPA during a balloon valvuloplasty procedure.